Macroscopic investigations on the afferent and efferent lymph vessels of the cervical superficial node and popliteal lymph node in akkaraman sheep - Sadettin Tıpırdamaz; Necdet Dursun; Hasan Erden; Memduh Gezici; İ. Hakkı Nur (Eurasian Journal of Veterinary Sciences)
In this study, numbers and the courses of the afferent and efferent lymph vessels of th&' cervical superficial node and popliteal lymph node were investigated in Akkaraman sheep. As a material, eight Akkaraman sheep were Used.